The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/met10070933
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Backing Plate Materials in Micro-Friction Stir Butt Welding of Dissimilar AA6061-T6 and AA5052-H32 Aluminum Alloys

Abstract: Thin sheets of lightweight aluminum alloys, which are increasingly used in automotive, aerospace, and electronics industries to reduce the weight of parts, are difficult to weld. When applying micro-friction stir welding (μ-FSW) to thin plates, the heat input to the base materials is considerably important to counter the heat loss to the jig and/or backing plate. In this study, three different backing-plate materials—cordierite ceramic, titanium alloy, and copper alloy—were used to evaluate the effect of heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Reinforcement particles in the MMC were chosen to be SiC and the AA6061 alloy was both the MMC matrix and the monolithic material, to which the MMC plate was friction stir welded. FSW was conducted in the present experiment on 8-mm-thick plates which were significantly thicker than other friction stir welded Al/Al MMC plates described in several previous publications [6][7][8][9][10][11][12]. The microstructure of the as-received and friction stir welded plates is characterized in this work using optical microscopy and scanning electron microscopy (SEM).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Reinforcement particles in the MMC were chosen to be SiC and the AA6061 alloy was both the MMC matrix and the monolithic material, to which the MMC plate was friction stir welded. FSW was conducted in the present experiment on 8-mm-thick plates which were significantly thicker than other friction stir welded Al/Al MMC plates described in several previous publications [6][7][8][9][10][11][12]. The microstructure of the as-received and friction stir welded plates is characterized in this work using optical microscopy and scanning electron microscopy (SEM).…”
Section: Introductionmentioning
confidence: 98%
“…Since Al-base MMCs are more expensive than traditional aluminum alloys, there is a clear economical reason to use them only in the most critical parts of a product, whereas other parts can be made of conventional monolithic alloys. This necessitates joining of dissimilar materials, which can conveniently be done using friction stir welding (FSW) [1][2][3][4][5][6]. In the FSW process, a rotating tool generates heat due to friction, which softens and plasticizes materials to be joined.…”
Section: Introductionmentioning
confidence: 99%
“…Existing literature has explored the use of various backing plate materials such as copper, mild steel, aluminium, titanium, asbestos, and granite to attain defect-free welds without resorting to secondary processing techniques like postweld heat treatment. [15][16][17][18][19][20][21] Open literature has investigated the utilization of diverse backing plates in conventional FSW, examining their impact on joint properties. The effect of using aluminium, steel, Ti-6Al-4V, and ceramic backing plates (BP) was studied for FSW of 25.4 mm thick AA6061 plates.…”
Section: Introductionmentioning
confidence: 99%
“…Dissimilar weld efficiency is typically measured against the weaker of the two parent materials (Bandhu, Kumar, Nishant, & Thakur, 2017;Park et al, 2020;Venkateswara Rao & Senthil Kumar, 2020). When considering 6 relevant 4 studies in the literature it was found that the weld efficiency of germane dissimilar materials varied between 42.9% and 94% for the most successful welds produced, with an average (of the 6 results considered) of 71.5%.…”
Section: Tensile Strength and Ductilitymentioning
confidence: 99%
“…Dissimilar weld efficiency is typically measured against the weaker of the two parent materials (Bandhu et al, 2017;Park et al, 2020;Venkateswara Rao & Senthil Kumar, 2020), however AA8090 and BS L165 have comparable minimum UTS specifications and extremely similar measured UTS values. The difference in measured UTS for the two parent materials falls within the uncertainty of the measurement (refer to sections 3.4.2, 4.1.3.2 and 4.2.3.2) and so the materials can be considered to have equivalent measured UTS (when compared with the relevant orientation).…”
Section: Tensile Testingmentioning
confidence: 99%